Efficient phrase search with reliable verification over encrypted cloud-IoT data - Wanshan Xu; Ze Zhu; Muhammad Irfan Khalid (PeerJ Computer Science)
Phrase search encryption enables users to retrieve encrypted data containing a sequence of consecutive keywords without decrypting, which plays an important role in cloud Internet of Things (IoT) systems. However, due to the sequential relationship between keywords in the phrase, phrase search and verification are more difficult than multi-keyword search. Furthermore, verification evidence is generated by the server in existing schemes, and cloud servers are generally considered untrustworthy, so the verification is unreliable. To address this, we propose an efficient phrase search scheme that supports reliable verification of search results, where blockchain is introduced to generate verification evidence and perform verification of the results. The immutable nature of blockchain guarantees the credibility of evidence and verification. During the verification, we use a multiset hash function to generate aggregated evidence, reducing storage and blockchain transaction costs. In addition, we design a novel composite index and discrimination algorithm based on homomorphic encryption, with which we can quickly identify phrases and improve search efficiency. Finally, we conducted security analysis and detailed experiments on our scheme, which proved that the scheme is secure and efficient.